Integrated Effect of Seed Priming and Inoculation on Growth and Yield of Maize (Zea Mays L.) - Majid Hussain Dayo,; Pir Ahmed Naqi Shah,; Asif Ali Kaleri,; Maira Raqeeb Tunio,; Danish Manzoor ,; Abdul Jabbar,; Sarang Ali Bhand,; Dad Jan,; Niaz Ahmad,; Arslan Nazeer Channa,; Urooj Rehmani, (Dialogue Social Science Review (DSSR), 2025)
Integrating effective seed treatments is pivotal for enhancing maize crop performance. This study explores the combined impact of seed inoculation with PGPR (Biozote Max) and seed priming with canal water (6hr) on the growth and yield of maize. Field experiments were conducted at the student’s experimental farm, department of Agronomy, Sindh Agriculture University Tandojam, utilizing a randomized complete block design in three replications. The treatments included untreated (Control), seed Inoculation with (PGPR), seed priming with canal water (6hr) and a combined seed priming with subsequent PGPR inoculation. Key growth parameters, including plant population, plant height, cobs plant-1, stem girth, biological yield, seed index and grain yield, were assessed. Statistical analyses revealed significant (P<0.05) impacts of seed treatments on maize crop growth and yield. Results demonstrated that the integrated treatment, involving seed priming followed by PGPR inoculation, significantly outperformed other treatments in terms of maximum plant population 16.77, plant height 226.21 cm, cobs plant-1 2.11, stem girth 3.51cm, biological yield 8095 kg ha-1, seed index, 297.74, grain yield 4.47 plot-1 and grain yield 3802 kg ha-1. Seed Inoculation with PGPR in-oculum (Biozote Max) ranked 2nd with plant population 14.76, plant height 212.88 cm, cobs plant-11.44, stem girth 2.70 cm, biological yield 7000 kg ha-1 seed index 293.57, grain yield 4.12 plot-1 and grain yield 3545.7 kg ha-1. However, minimum performance was observed in Untreated (Control) with lowest plant population 9.05, plant height 166.72 cm, cobs plant-1 1.00, stem girth 2.37 cm, biological yield 5582 kg ha-1, seed index 243.70, grain yield 3.07 plot-1 and grain yield 3039.7 kg ha-1. These findings provide valuable insights for optimizing seed treatment strategies in maize cultivation, with implications for enhancing crop productivity and sustainability.